Analisis Sektor Basis dan Non Basis Serta Daya Saing Ekonomi Terhadap Peningkatan Pertumbuhan Ekonomi Kota Bandar Lampung: Indonesia - Endriyani, Febila (Universitas Negeri Surabaya, 2023)
Economic growth is an increase in the ability of an economy to produce goods and services. In other words, economic growth refers more to quantitative changes and is usually measured using gross domestic product data or per capita output income. The purpose of this study is to analyze which sectors include the base and non-base sectors and how economic competitiveness in increasing economic growth in the city of Bandar Lampung. This research uses quantitative research methods with Location Question (LQ), Shift Share and Typology Klassen analysis tools. The results of the research based on the results of the Location Question analysis show that there are 15 basic sectors and 2 other economic sectors which are non-base sectors in Bandar Lampung City. The research results from the Shift Share analysis show that almost all economic sectors in Bandar Lampung City have a positive Differential Shift value, which means that these economic sectors have strong competitiveness or have a high competitive advantage compared to the same sector in the economy. National. The results of the study from the Klassen Typology analysis show that there are 5 developed and rapidly growing sectors in Bandar Lampung City and there are 12 Growing Sectors.